(untitled) (Medicine Today, 2017)
The determination of infarct related artery in acute inferior myocardial infarction is extremely important for the prediction the amount of myocardium at risk and guide decisions regarding urgency of revascularization. Urgent decision may facilitate management and prevention of complication. Our objective was to Identification of the infarct related artery involving either right coronary artery (RCA) or left circumflex artery (LCX) in acute inferior wall myocardial infarction using electrocardiographic criteria and comparing with angiographic finding. This prospective, observational study was done in Chittagong Medical College Hospital from June 2013 to May 2014. A total of 112 Patients with acute inferior myocardial infarction were included in this study. The electrocardiogram of these patients evaluated for ST segment elevation in lead III exceeding that in lead II (i.e. a ratio of ST elevation in lead III/elevation in lead II > 1) and S/R wave ratio > 0.33 plus ST segment depression > 1 mm in lead aVL as a prediction for right coronary artery occlusion. If criteria are negative, LCX obstruction is likely. Coronary angiogram was done within 2-6 weeks in cath lab, department of cardiology, CMCH to identify the culprit artery. The infarct related artery (IRA) was identified from total occlusion or significant stenosis (> 70%) of the RCA or LCX or their major branches, or from arteriographic evidence of intraluminal thrombosis. To minimize the chance of misclassifying the culprit artery, patients with significant stenosis of both the RCA and the LCX were excluded from the study. The study population consisted of 112 patients (94 male and 18 female) with a mean ± SD age of 51 ± 8.6 years. On coronary angiography, the culprit artery was shown to be the RCA in 92 patients and the LCX in 20 patients. It was evident that the degree of ST segment elevation in lead III was significantly higher in right coronary artery group (92 patients) vs left circumflex group (20 patients) 3.16±1.14mm vs 1.35±0.24mm (p<0.001) respectively. While its comparable in lead II 2.18±0.95mm vs 1.7±0.34mm (p>0.05). In respect to leads AVL, we found that deeper ST segment depression was in right coronary artery group as compared to left circumflex group 1.11±0.25mm vs 0.2 ±0.34mm (p<0.001). ECG parameters for implicating the RCA were a higher ST elevation in lead III than lead II (specificity 98%, sensitivity 97%) and an S/R wave ratio > 0.33 plus ST segment depression > 1 mm in lead aVL (specificity 96%, sensitivity 95%). Absence of these criteria was associated with LCX occlusion (specificity 100%, sensitivity 85%). It is possible to predict the culprit artery whether right coronary artery or left circumflex by examining the surface electrocardiography in patients with acute inferior myocardial infarction. Medicine Today 2017 Vol.29(2): 33-37